Aspek Pidana Dalam Hukum Keluarga Dan Penyelesaiannya Pada Lembaga Hukum Di Indonesia - Zulham Wahyudani; Oyo S. Mukhlas; Atang Abdul Hakim (IAIN Langsa, 2023)
Referring to Muslim countries outside Indonesia, several progressive legal regulations are obtained, because they display the jināyat (Penal Code) of their marriage law. Social facts in Indonesia identify the criminal aspects related to violations in marriage, such as unrecorded marriages, illegal polygamy, interfaith marriages, divorce, infidelity, domestic violence, or fraud. It has caused enormous legal and social problems, especially those related to the protection of women and children right. The purpose of this study is to analyze the criminal aspects reasoning in family law and its settlement in legal institutions in Indonesia. This research was conducted based on literature study by collecting data and theoretical foundations related to aspects of criminal acts in marriage law. The results showed that, firstly, the criminal aspects of family law in Indonesia are included in the Penal Code (KUHP) Article 279, which includes violations of law or criminal aspects of marriage law that harm other people. Secondly, the settlement of criminal aspects in family law in legal institutions in Indonesia is the expansion of several religious courts authority. For Instance, the authority of the Syar'iyah Court in Aceh is an inevitability. Considering that everything that is regulated under the religious courts authority, both concerning marriage, inheritance, waqf, zakat, to the issue of shari'ah economics, all of which are that has been attached to Muslim society.